The Cost of Coordination Failures: Impacts on Urban Development Projects and Citizen Services in Bangladesh - Md Zia Uddin (HM Publisher, 2025)
Rapid urbanization in Bangladesh places significant pressure on City Corporations to effectively plan and implement urban development projects, often in collaboration with national agencies. However, coordination failures are prevalent, leading to significant costs and hindering urban development. This study investigates the challenges in service delivery coordination faced by City Corporations in Bangladesh, focusing on Cumilla and Dhaka as case studies to understand the complexities of coordination in varying urban contexts. A qualitative research approach was employed, involving semi-structured interviews with 110 stakeholders across both cities. This included 40 City Corporation officials, 30 government agency representatives, and 70 community representatives, ensuring a multi-faceted understanding of the issue. Data was analyzed using thematic analysis and interpretive techniques to identify recurring patterns and themes related to coordination challenges, their consequences, and potential solutions. Rigor and trustworthiness were ensured through data triangulation, member checking, and reflexivity. The study identified several key coordination challenges, including dysfunctional coordination committees, power struggles between City Corporations and national agencies, non-compliance with regulations, unclear roles and responsibilities, dual control over tasks, breaches of agreements, political interference, self-serving leadership, and inadequate corrective measures. These challenges hinder project progress and negatively impact citizens, leading to subpar work quality, project delays, funding withdrawals, poor service delivery, financial waste, and increased public distress. In conclusion, this study underscores the urgent need for improved coordination mechanisms, accountability frameworks, and capacity-building initiatives to enhance urban development and service delivery in Bangladesh.